Behavioral and Psychological Symptoms Impact Clinical Competence in Alzheimer’s Disease - Bertrand, Elodie; van Duinkerken, Eelco; Landeira-Fernandez, J.; Dourado, Marcia C. N.; Santos, Raquel L.; Laks, Jerson; Mograbi, Daniel C. (Frontiers in Aging Neuroscience, 2017)
Decision-making is considered a fundamental aspect of personal autonomy and can be affected in psychiatric and neurologic diseases. It has been shown that cognitive deficits in dementia impact negatively on decision-making. Moreover, studies highlighted impaired clinical competence in neuropsychiatric disorders, such as schizophrenia and bipolar disorder. In this context, the current study explored the relationship between behavioral and psychological symptoms of dementia (BPSD) and clinical competence, especially the capacity to consent to treatment, in Alzheimer's Disease (AD). Seventy-one patients with mild to moderate AD participated, completing assessments for capacity to consent to treatment, general cognition and neuropsychiatric disturbances. For each neuropsychiatric symptom, patients with and without the particular disturbance were compared on the different subscales of the MacArthur Competence Tool for Treatment (Understanding, Appreciation, Reasoning and Expression). The results showed that patients presenting delusions, as well as apathetic patients, had a lower ability to express a clear treatment choice compared to patients without these symptoms. By contrast, patients with dysphoria/depression had higher scores on this variable. Additionally, AD patients with euphoria had more difficulties discussing consequences of treatment alternatives compared to patients without this disturbance. None of the differences were confounded by global cognition. There were no between-group differences in clinical decision-making for patients with hallucinations, agitation/aggression, anxiety, irritability, disinhibition and aberrant motor behavior. These findings highlight the importance of taking BPSD into account when assessing decision-making capacity, especially clinical competence, in AD. Furthermore, reducing BPSD may lead to better clinical competence in patients with AD, as well as to improvements in patients and caregivers' quality of life.